EFEKTIVITAS PEMBELAJARAN GENETIKA DALAM PENINGKATAN KESADARAN PENYAKIT GENETIK PADA SISWA KELAS 11 MAN 1 MEDAN - Miftahul Khairani; Billah Afrianti; Diva Raya Kinanti Rambe; Kayla Nur Hafizhah; Syntia Zeyrani Nahombang (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Genetic disease is a health condition caused by changes or mutations in a person's genetic material. Some examples of commonly known genetic diseases include thalassemia, cystic fibrosis, and Huntington's disease. This research was carried out to determine the level of awareness of class 11 students at MAN 1 Medan regarding genetic diseases and to provide an understanding of the importance of preventing genetic diseases. The method used in this research is the survey method. The results of the basic knowledge survey about genetics were that 85% of students stated that they had studied genetics at school and 60% of students stated that genetics material was discussed quite often in biology lessons. In understanding genetic diseases, 70% of students know what genetic diseases are and the most well-known examples of genetic diseases are Thalassemia and Hemophilia. Regarding the effectiveness of genetics learning, 75% of students felt that genetics learning helped them understand genetic diseases and the most effective method according to students was laboratory practicum (50%), followed by learning videos (30%). In terms of increasing awareness, 65% of students felt more aware of the importance of checking for genetic conditions after studying genetics and 80% of students considered that genetics learning at their school was good or very good in increasing awareness about genetic diseases. So it can be concluded that genetic diseases are health conditions caused by changes in a person's genes or chromosomes.